HLY1104 Winter Cruise Zooplankton Morphometrics ... - Ashjian, Carin; Campbell, Robert; Okkonen, Stephen (NSF Arctic Data Center, 2014)
Zooplankton size data collected during the USCGC Healy cruise to the Chukchi, Beaufort, and Bering Seas in Nov. - Dec. 2011. See Readme file for methods. ...